Caregiver burden among working women and homemakers taking care of psychiatric patients - Navneet Kaur (Wolters Kluwer Medknow Publications, 2021)
Background: Caregiver burden is defined as the physical, psychological or emotional, social, and financial problem that can be experienced by the members of family caring for impaired person. In India, women are twice more likely to become caregivers than men, despite emergence of men as caregivers. Aim: The aim of the study is to assess burden of illness among working women and homemakers taking care of psychiatric patients. Materials and Methods: This hospital-based, descriptive, cross-sectional comparative study was conducted on the caregivers who were recruited from outdoor patient department of psychiatry department of a tertiary care hospital attached to a medical college. Women who were 30–45 years old, working or homemakers and who were taking care of psychiatric patients diagnosed with schizophrenia and Bipolar affective disorder (BAPD) of either sex. Caregivers were first-degree relatives of patients. Sociodemographic data were recorded using a special performa and caregiver burden was assessed using caregiver burden questionnaire. Results: Overall mean caregiver burden scores in Group 1 and Group 2 were 55.66 ± 4.09 and 58.16 ± 3.97, respectively, with statistically significant difference (P < 0.05). Conclusion: Caregiver burden was more among working women compared to homemaker women.